THE BACHELOR OF PHYSICAL EDUCATION PROGRAM IN HIGHER EDUCATION INSTITUTIONS TOWARDS THE DEVELOPMENT OF AN ENHANCED CURRICULUM - Lubis, Ferdie T (PEOPLE: International Journal of Social Sciences, 2019)
This research study has two main foci: the analysis of the Bachelor of Physical Education curriculum of five selected Higher Education Institutions and analysis of the responses of the interviews that spelled out the Bachelor of Physical Education Program towards its enhancement. The five curricula that were reviewed were designed in their unique way because they were based on the vision, mission, goals and objectives of the school. Similarities and differences were analyzed to find out the status of the curricula. Based on the interviews conducted, all five schools agreed to increase the number of Professional Education subjects. They all agreed also to include sports, dance, sports coaching and officiating subject to strengthen their program and to prepare their students to become competent Physical Education educators in the future. It was found out that their curricula for Bachelor of Physical Education had provided a wide and clear understanding of Physical Education needed by the students. It was also found out that the best practices in the said Higher Education Institutions could be derived from a thorough analysis of their similarities and differences in their curricular offerings to develop an enhanced curriculum for Bachelor of Physical Education for Teachers.